FUNGSI KONSTRATIF SAPAAN DI DALAM MASYARAKAT LAMPUNG DAN KOMERING - Rafa Maritza Herga; Marya Utari; Mulyanto Widodo; Rahmat Prayogi (STKIP Pesisir Selatan, 2025)
This study examines the role of1 greetings in shaping social identity, building a sense of group unity, and creating harmony among 2people in Lampung and Komering communities. In this context, greetings not only serve as conversation starters but also as tools to strengthen cultural rules, social hierarchical structures, and community integration in the Lampung region. This study uses a communication ethnography and discourse analysis approach. Data were collected through direct observation, in-depth interviews with local residents, and text analysis of daily interactions. The results show that in Lampung society, greetings tend to be formal and hierarchical, such as using the words